Suppression of SARS-CoV-2 nucleocapsid protein dimerization by ISGylation and its counteraction by viral PLpro - Bang, Wonjin; Kim, Jaehyun; Seo, Kanghun; Lee, Jihyun; Han, Ji Ho; Park, Daegyu; Cho, Jae Hwan; Shin, Donghyuk; Kim, Kyun-Hwan; Song, Moon Jung; Ahn, Jin-Hyun (Frontiers in Microbiology, 2024)
Protein modification by the ubiquitin-like protein ISG15 (ISGylation) plays a crucial role in the immunological defense against viral infection. During severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, innate immune signaling proteins are ISGylated, facilitating innate immunity. However, whether SARS-CoV-2 proteins are direct substrates for ISGylation remains unclear. In this study, we investigated whether SARS-CoV-2 proteins undergo ISGylation and whether ISGylation affects viral protein function. Co-transfection ISGylation analysis of SARS-CoV-2 proteins showed that the nucleocapsid (N) protein is ISGylated at several sites. Herc5 promoted N ISGylation and interacted with N, indicating that Herc5 acts as an E3 ligase for N ISGylation. Lys-261 (K261) within the oligomerization domain of N was identified as a potential ISGylation site that is necessary for efficient ISGylation of N. K261 is positioned at the center of the dimer interface in the crystal structure of the C-terminal domain dimer and the ISGylated form of N showed reduced protein dimerization in pull-down analysis. Importantly, a recombinant virus expressing K261R mutant N showed enhanced resistance to interferon-β treatment compared to its parental virus. We also found that viral PLpro removes conjugated ISG15 from N. Our findings demonstrate that ISGylation of SARS-CoV-2 N inhibits protein dimerization, resulting in viral growth more susceptible to type I interferon responses, and that viral PLpro counteracts this ISG15-mediated antiviral activity by removing conjugated ISG15 from N.